Structural transect through Silurian turbidites of the Fredericton Belt southwest of Fredericton, New Brunswick:: the role of the Fredericton Fault in late Iapetus convergence - Park, Adrian; Whitehead, James (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT Excavations along the 23 km stretch of the Longs Creek to Fredericton section of the new Trans-Canada Highway created new exposures affording a transect through part of the Fredericton Belt west of, and including, the Fredericton Fault. This transect lies entirely in the Burtts Corner beds of the Silurian Kingsclear Group, revealing a multi-deformation history. Earliest structural elements in the turbidites include a slaty cleavage (S1) that is close to being bedding-parallel in most places. No F1 fold closures have been identiﬁed, but small enclaves of inverted bedding imply that such structures exist but are of limited scale and restricted occurrence. The most conspicuous structures are upright to overturned, open to tight F2 folds with chevron proﬁles, a locally well-developed axial planar slaty cleavage (S2) and a related crenulation lineation on S1 (L12). These folds have curvilinear hinge-lines that show an increase in curvilinearity toward the Fredericton Fault, coincident with a tightening of the interlimb angle. Lineations related to layer-parallel slip during F2 fold generation remain constant implying the changing geometry is a consequence of changing bulk strain rather than fold interference. Post-F2 structures include a sparsely developed set of chevron folds with horizontal axial planes (F3) and a poorly developed axial planar slaty cleavage (S3). At least two sets of late kinks have also been noted. Systematic variations in style and form of the F2 folds suggest a relationship with the precursor to the Fredericton Fault, implying a role for this structure in Acadian orogenic deformation starting out as a sub-horizontal detachment prior to rotation into its current vertical attitude. This low-angle dip-slip phase is related to the convergence of Avalonia* with the Miramichi terrane (the remains of the Ordovician Miramichi arc, incorporated into the Brunswick subduction complex by the mid-Silurian), and preceded the behaviour of the Fredericton Fault as an orogen-parallel strike-slip feature in later Acadian orogenesis. * Avalonia' here refers to the composite terrane in southern New Brunswick consisting of Avalonia sensu stricto and a number of peri-Gondwanan terranes, see Barr and White (1996, 1999), or a southern terrane that is a composite of Avalonia and Ganderia (see for instance, van Staal et al. 2002). This contribution does not present any data allowing a choice between these models.